Dinamika Retoris dan Konstruksi Intelektualitas Anies Rasyid Baswedan di Mimbar Akademik: Sebuah Kajian Retorika Aristoteles - Afdal, Adristi; Septiana, Ika (J-LELC: Journal of Language Education, Linguistics, and Culture, 2026)
The primary focus of this research is to examine how persuasive language is employed not merely to convey information, but as a strategic instrument for building image and social influence within an academic platform. This study adopts a descriptive qualitative approach using rhetorical analysis based on Aristotle’s rhetorical triad of ethos, pathos, and logos. The data consist of persuasive utterances collected through close listening and verbatim transcription of an official video recording. The analysis focuses on the use of diction, metaphor, and argumentative structure that contribute to shaping audience perception. The findings reveal that the three rhetorical dimensions are orchestrated systematically, beginning with the construction of intellectual ethos and speaker authority in the early stages of the discourse, followed by the management of pathos in a moderate and reflective manner to foster emotional engagement with the audience, and reinforced by logos through logical reasoning and academically nuanced argumentation. These findings underscore that persuasive effectiveness in public academic communication largely depends on the dynamic integration and function of the three rhetorical elements. This study contributes to the development of discourse analysis and rhetorical studies within the context of educational communication in Indonesia.